(untitled) (Revista Brasileira Multidisciplinar, 2023)
The present study evaluated the factors associated with physical activity among adults in a municipality of the Jequitinhonha Valley, Minas Gerais, Brazil. A household survey was conducted, using a questionnaire to assess physical activity, with a sample of 403 subjects aged ≥ 18 years. A survey of the distribution of the health fitness center program in the region was conducted. Statistical analysis was performed using Pearson’s chi-square test. Among the 31 municipalities in the Jequitinhonha Macroregion, 14 adhered to the health fitness center program. Of those eligible, 31.7% of males and 20.6% of females engaged in physical activity. It was observed association to physical activity 3 days per week (considered active) with body mass index between 25 ≤ BMI < 30 (overweight): PR 1.42, CI (1.05, 1.92); BMI ≥ 30 (obese): PR 1.47, CI (0.99, 2.17). For physical inactivity (10 minutes per week), there was also an association with body mass index, with 25 ≤ BMI < 30 (overweight): PR 1.30, CI (1.04, 1.64); BMI ≥ 30 (obese): PR 1.40, CI (1.03, 1.89). The results of the present study show that there is support for the health fitness center in the region, as well as a difference between the prevalence of physical activity among men and women, and an association with the body mass index. In regions with low municipal urban development index, the health fitness center program is a health promotion integration strategy for reducing sedentary behavior.